The impacts of rail freight rate changes on regional economies, modal shift, and environmental quality in Korea - Lee, HyunKyung; Kim, HongBae (International Journal of Urban Sciences, 2018)
Korail is a typical government-owned enterprise in Korea and plans to raise its rail freight rates by 10-15% in order to offset the deficit in its operating costs. When this policy goes into effect, it will have an impact on regional economies of Korea. There will be subsequent effects on the environmental quality due to a shift in demand from rail to other transportation modes including road transportation. This paper attempts to evaluate the impacts of the rail freight rate policy on Korea. The policy is specifically analyzed in terms of three impacts: (i) on regional economies, (ii) on modal choice, and (iii) on CO 2 emissions. A simple multi-region price input-output model and a multi-regression analysis model are employed for the analysis. This paper shows that there is no trade-off between environmental quality and economic efficiency in the case of Korail. In other words, the policy will generate a lose-lose outcome rather than a win-win situation for both regional economies and environment in Korea.